The impact of using the Previous and acquired knowledge strategy in increasing the achievement for the eighth-grade students at al-aqaba governorate in Jordan - Al-Maayta, Hiam Mohamed (Journal of Educational and Psychological Sciences, 2019)
The study aimed to identify the impact of using the Previous and acquired knowledge strategy in increasing the achievement for eighth grade students, the study depends on semi-experimental approach. The sample of study consists of tow section of 8th grade in Al-thamnah primary school for girls in directorate of aqaba during the year 2018-2019,and the random assignment (1) as an experimental group will be 30 students and the division (2) as a group of officers formed of 30 students.In order to achieve the objective of the study , the study tool was constructed to test the achievement and after verifying its validity and stability it was applied to the sample of the beginning of the study and after the study group.The result of the single unit variance (ANCOVA) showed that there were statistically significant differences between the student response to the test of the acquisition of achievement due to the variable method of teaching and the strategy of the Previous and acquired knowledge comparing with usuall method.The researcher recommended the possibility of training teachers to use strategy of the Previous and acquired knowledge and model in teaching science because it proved its effectiveness and recommended conducting study on the introduction of other teaching methods of comparison in the achievement.
Keywords: impact; prior and acquired knowledge strategy; increasing achievement; science topic